Kontribusi Perhatian Orang Tua Dan Keadaan Ekonomi Keluarga Terhadap Minat Melanjutkan Studi Ke Perguruan Tinggi Pada Anak Kelas XII SMA/SMK (Studi Kasus Di Kecamatan Teras,Kabupaten Boyolali) - ANJARNINGTIYAS, RIRI, Drs. Sudarto, M.M (2016)
The research purpose is to knowing an influence between independent variable to dependent variable. Independent variable in this research is parental supervision and family economic circumstances. Meanwhile dependent variable in this research is interest to continue their studies to university. The research method. This research genre is associative quantitative research. The research design is using case study. Population of the research is 144 children in grade XII senior high school. Research sample is 95. There is research instruments by questionnaire and documentation. The research testing, use precondition testing and hypotheses testing. The precondition 2 testing consists of normality test, linearity test and multicolinearity test. The hypotheses testing consist of doubled regression analysis, partial t-test, F test, coefficient determination test, relative contribution and effective contribution. The result of the research showing there is a significant influence between parental supervision and family economic circumstances on the interest to continue their studies to university in children grade XII in senior high school Teras district, Boyolali regency. Based on counting result, with doubled regression analysis gain equation Y = 77,689 + 0,278X1 + 0,248X2. With partial testing use t-tes, gain t-count for parental supervision 2,516 and gain t-count for family economic circumstances 2,073. With the result of t-count > t-table 1,986, then can be conclude there is an influence between independent variable individually against dependent variable. With the result of F-count 37,462 > F-table 3,095 so there is an influence between independent variable togetherly against dependent variable. Based on coefficient determination testing, gain result 0,449. Because of that, the amount of interest to continue their studies to university which is influenced by parental supervision and family economic circumstances giving contribution as big as 44,9 %.